Diastereoselective Mannich reactions of pseudo-C2-symmetric glutarimide with activated imines - Ishikawa, Tatsuya; Kawasaki-Takasuka, Tomoko; Kubota, Toshio; Yamazaki, Takashi (Beilstein Journal of Organic Chemistry, 2017)
As an extension of the boron enolate-based aldol reactions, the oxazolidinone-installed bisimide 1a from 3-(trifluoromethyl)glutaric acid was employed for Mannich reactions with tosylated imines 2 as electrophiles to successfully obtain the corresponding adducts in a stereoselective manner.
Keywords: chiral oxazolidinones; diastereoselectivity; Mannich reactions; pseudo-C2 symmetry; trifluoromethyl

(untitled) - Yamazaki, T.; Haga, J.; Kitazume, T.; Nakamura, S. (Chem. Lett., 1991)

(untitled) - Yamazaki, T.; Haga, J.; Kitazume, T. (Chem. Lett., 1991)

(untitled) - Shinohara, N.; Haga, J.; Yamazaki, T.; Kitazume, T.; Nakamura, S. (J. Org. Chem., 1995)

(untitled) - Watanabe, Y.; Yamazaki, T.; Kubota, T. (Org. Lett., 2010)

(untitled) - Watanabe, Y.; Yamazaki, T.; Kubota, T. (Org. Lett., 2010)

(untitled) - Gao, X.; Han, H.; Krische, M. J. (J. Am. Chem. Soc., 2011)

(untitled) - Linclau, B.; Cini, E.; Oake, C. S.; Josse, S.; Light, M.; Ironmonger, V. (Angew. Chem., Int. Ed., 2012)

(untitled) - Ikeuchi, K.; Ido, S.; Yoshimura, S.; Asakawa, T.; Inai, M.; Hamashima, Y.; Kan, T. (Org. Lett., 2012)

(untitled) - Arend, M.; Westermann, B.; Risch, N. (Angew. Chem., Int. Ed., 1998)

(untitled) - Huguenot, F.; Brigaud, T. (J. Org. Chem., 2006)

(untitled) - Han, X.; Kwiatkowski, J.; Xue, F.; Huang, K.-W.; Lu, Y. (Angew. Chem., Int. Ed., 2009)

(untitled) - Mei, H.; Dai, Y.; Wu, L.; Soloshonok, V. A.; Han, J.; Pan, Y. (Eur. J. Org. Chem., 2014)

(untitled) - Yin, L.; Brewitz, L.; Kumagai, N.; Shibasaki, M. (J. Am. Chem. Soc., 2014)

(untitled) - Franck, X.; Seon-Meniel, B.; Figadère, B. (Angew. Chem., Int. Ed., 2006)

(untitled) - Evans, D. A.; Ennis, M. D.; Mathre, D. J. (J. Am. Chem. Soc., 1982)

(untitled) - Cieplak, A. S.; Tait, B. D.; Johnson, C. R. (J. Am. Chem. Soc., 1989)

(untitled) - Cieplak, A. S. (Chem. Rev., 1999)

(untitled) - Johnson, F. (Chem. Rev., 1968)

(untitled) - Hoffmann, R. W. (Chem. Rev., 1989)